Optimal Multi-Field Functional Electrical Stimulation Parameters for the “Turn on the Light” Task and Related Upper Limb Kinematics Repeatability in Post Stroke Subjects - Pinheiro De Sousa, Andreia Sofia (2022)
To characterize the optimal Functional Electrical Stimulation (FES) parameters that assist the “turn on the light” task (TOTL) on post stroke participants and to analyze the related upper limb (UL) kinematics repeatability.